1984
DOI: 10.1128/jcm.19.4.516-520.1984
|View full text |Cite
|
Sign up to set email alerts
|

Relative frequency of rotavirus subgroups 1 and 2 in Venezuelan children with gastroenteritis as assayed with monoclonal antibodies

Abstract: Monoclonal antibodies recently developed against the 42,000-dalton protein of two rotavirus strains were used in an enzyme-linked immunosorbent assay to determine the subgroup specificity of 252 specimens collected during a 45-month period from Venezuelan children with rotavirus gastroenteritis. Subgroup 2 rotavirus was shed by 85% of the children, whereas only 14% shed subgroup 1 rotavirus (one-half of them in a 3-month period). No differences were found in the occurrence of fever and vomiting between childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
24
1

Year Published

1985
1985
1991
1991

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 18 publications
5
24
1
Order By: Relevance
“…Greenberg of Stanford University. Subgrouping of HRV isolates was done as described by White et al [1984]. Hyperimmune serum was produced in rabbits immunized with the prototype strains Wa (subgroup 11) and DS-1 (subgroup I).…”
Section: Subgrouping Of Hrv Isolatesmentioning
confidence: 99%
“…Greenberg of Stanford University. Subgrouping of HRV isolates was done as described by White et al [1984]. Hyperimmune serum was produced in rabbits immunized with the prototype strains Wa (subgroup 11) and DS-1 (subgroup I).…”
Section: Subgrouping Of Hrv Isolatesmentioning
confidence: 99%
“…In our study, the constant frequency of infections at the obstetric wards, contrasting t o the seasonal variations seen among older children with symptomatic infections (l), indicate endemicity of the neonatal infections. Furthermore, the distribution of subgroups at the two wards, used only for obstetric patients, differed from what is seen in the community (9,12), possibly a reflexion of an endemic circulation in the wards of rotavirus strains of subgroup I. The mothers of the infants were a source of infection in 10% of the cases.…”
Section: Discussionmentioning
confidence: 85%
“…Two subgroups of rotavirus have been described (9, lo), and recently a tentative third subgroup was detected (9,11). Subgroup I1 seems to be the predominant cause of childhood gastroenteritis (9,12). There is a difference among strains encountered in the community to those appearing in nurseries and special care baby units, as seen by polyacrylamide electrophoresis (13).…”
mentioning
confidence: 99%
“…Although one study has recently reported a subgroup 1 rotavirus with a long electropherotype (NAKAGOMI et al, 1985), we have assumed that the electropherotypic analysis can be used to give a presumptive diagnosis of subgroup specificity, and have analysed the-clinical feat&es -of 'the two -groups. The one similar studv had shown no differences in severity of fever, vomifing or diarrhoea between the two subgroups, although the syndrome was thought to be of longer duration with subgroup 2 rotaviruses, which the authors suggested might indicate that subgroup 2 rotaviruses were more virulent (WHITE et al, 1984). In most studies of diarrhoea subgroup 2 roiavirusks predominate, again suggesting thit &ese viruses are more virulent (YOLKEN et al, 1978;WHITE et ul., 1984), although rotavirus subgroup i outbreaks have also been reported (ALBERT et al, 1983).…”
Section: Discussionmentioning
confidence: 95%